(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
The aim of this article is to analyse self-publishing trends of Lithuanian cultural periodicals focusing on the historical and contemporary contexts. The article provides an overview of the reasons for historical cultural periodical self-published texts, known as samizdats, to appear, as well as their publishing and circulation trends in Lithuania. It also analyses what contemporary cultural self-publishing is: whether it is a completely independent, logical consequence of the digital age, which emerged under favourable circumstances, or if it can be characterized as having something in common with the past experiences. The most active years of the periodical underground press publishing in Soviet Lithuanian self-publishing development were between 1975 and 1981. Self-published texts ideologically diverged into three main directions: religious, civic, and cultural-artistic. A total of 22 publications were being published for a longer or shorter period of time. While analysing contemporary cultural self-publishing topics, the report focuses only on online cultural texts, irrespective of the printed ones. Survey method was used to find out how much and in what aspect modern Internet users perceive historical periodical self-publishing, and how and in what aspect they value modern cultural self-published texts. The results show that 18-35-year-old respondents have not acquired the skills necessary to analyse samizdat publishing. They associate the word self-publishing with digital texts only, which due to favourable conditions spread easily through social networks and blogs. In the era of advancing computer technologies and the Internet, every person who has the time and desire may become a developer, an author, or at least a disseminator of information: this tradition is becoming more and more topical and quite frequently – an almost self-evident phenomenon.